2019
DOI: 10.1212/nxi.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab for progressive multifocal leukoencephalopathy due to primary immunodeficiency

Abstract: Progressive multifocal leukoencephalopathy (PML) is a devastating demyelinating disease of the CNS, which develops almost exclusively in immunocompromised patients and is caused by JC virus (JCV), a common polyomavirus. 1 So far, treatment efficacy is only modest if the compromised immune system cannot be restored. 2-4 A potential treatment target is the programmed cell death protein 1 (PD-1) whose expression on CD4 + and CD8 + T lymphocytes has been shown to be elevated in patients with PML. Moreover, blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…In summary, nivolumab therapy did not prevent the detrimental clinical course of PML in a patient with SS, nor was a viral clearance induced. In synopsis with previously published cases [2][3][4][5][6][7] neither viral load in CSF at baseline nor patient age nor the number of months between PML onset and start of PD1I seem to correlate with clinical improvement. It is tempting to speculate that the comparatively low PD-1 expression at baseline and overall lymphopenia prevented a more favorable response in this case.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In summary, nivolumab therapy did not prevent the detrimental clinical course of PML in a patient with SS, nor was a viral clearance induced. In synopsis with previously published cases [2][3][4][5][6][7] neither viral load in CSF at baseline nor patient age nor the number of months between PML onset and start of PD1I seem to correlate with clinical improvement. It is tempting to speculate that the comparatively low PD-1 expression at baseline and overall lymphopenia prevented a more favorable response in this case.…”
mentioning
confidence: 64%
“…Immune checkpoint blockade stimulates immune function and has been suggested to reinvigorate viral clearance in PML patients by expanding JCV-specific T cells [1]. Among the first 13 published PML patients treated with programmed cell death 1 inhibitors (PD1I) eight showed a mild to marked treatment response [2][3][4][5][6][7]. The underlying conditions ranged from chronic lymphocytic leukemia, AIDS, non-Hodgkin lymphoma, idiopathic lymphopenia, variable immune deficiency, Hodgkin lymphoma, B-cell lymphoma to primary and combined immunodeficiency.…”
mentioning
confidence: 99%
“…Five of their 8 patients did well, but the remainder, despite effective PD-1 suppression, failed to establish an anti-JC virus T-cell response. Recently, Kuepper et al 2 published a case of primary immunodeficiency with PML who demonstrated a dramatic reduction in PD-1 expression with pembroluzimab, but the patient still died.…”
mentioning
confidence: 99%
“…One was considered to be a good candidate for the drug (young age, with a primary immunodeficiency syndrome, not previously treated with immunosuppression, limited MRI lesions, and low CSF viral load), was treated with PD1-ab at very early stage of the PML, and received more doses than those reported in patients who improved, but had relentless progression to death. 11 The second case had several immunosuppressive disorders, a very high viral load, and died after 2 infusions of the PD1-ab. An interesting observation was that this patient had fewer progenitor-exhausted T cells and more terminally exhausted T cells compared with a previously reported patient who had a favorable outcome.…”
mentioning
confidence: 99%